Industrial Recycling of Scrap Copper Cables and Wires: Combining Cold and Hot Treatments for Maximum Recovery and Minimal Emissions - O. Choukri; E. Mohsine; S. Taibi (Archives of Foundry Engineering)
With the increasing amount of electrical cable and wire scrap, copper recycling has become a priority to conserve natural resources and reduce environmental impact. This study presents an innovative process for recycling copper wire and cable of various types, including greased ones. The process combines cold and hot treatments to maximise metal recovery while minimising polluting emissions. Initially, the cables are stripped and the PVC sheaths and other components are separated. Subsequently, these cables are subjected to pyrolysis in a hermetical furnace operating under an inert atmosphere, ensuring the absence of toxic emissions. The pyrolysis, carried out at temperatures between 500 °C and 600 °C, decomposed the insulating materials while minimising copper oxidation. A 100 kg sample of wire and cable pyrolysed at 540 °C was melted in an Indian foundry using the Upcast process to produce 8 mm oxygen-free copper rods. The electrical conductivity measurement of these rods showed a value of 98.2% IACS, making them suitable for many applications, especially electrical ones. The copper recovery rate reached a maximum value of 99.5%, demonstrating the effectiveness of the process. This sustainable process, suitable for small and medium foundries, offers an efficient and environmentally friendly solution for copper cables recycling.